Fulfilment of Minimum Acceptable Diet as Dominant Factor in Wasting in Children Aged 6–23 Months in Central Jakarta, Indonesia, 2019 - Ervida Andina; Madinar Madinar; Endang Laksminingsih Achadi (Faculty of Public Health Universitas Indonesia, 2021)
AbstractWasting is a form of acute malnutrition characterized by significant and rapid weight loss resulting from inadequate food intake and infectious diseases. This study was to investigate the factors associated with wasting in children aged 6–23 months and the dominant factor among these. The study followed a cross-sectional study design. A total sample of 261 children was selected using multistage random sampling from 13 integrated healthcare centres in six administrative villages located in three sub-districts of Central Jakarta. Data was collected by measuring body weight and height and questionnaires completed through interviews carried out by trained data collectors. This study shows that the prevalence of wasting in children aged 6–23 months in Central Jakarta is 6.9%. Based on logistic regression analysis, fulfillment Minimum Acceptable Diet (MAD) (OR=3.2 90% CI 1.1-9.5) was found to be the dominant factor in wasting after controlling by mother's level of education (OR=1.7 90% CI 0.7–4.2) and the level of family income (OR=2.9; 90% CI 0.9-8.9). This research shows that there is a need for improvement of maternal behaviour in providing appropriate care for children. Based on this research, we recommend that intervention on appropriate breastfeeding and complementary feeding practices be strengthened, especially for mothers with low levels of education and family income.AbstrakWasting adalah salah satu bentuk malnutrisi akut yang ditandai dengan penurunan berat badan yang signifikan dan cepat akibat asupan makanan yang tidak memadai dan penyakit infeksi. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan wasting pada anak usia 6-23 bulan dan untuk mengetahui faktor dominan di antaranya. Penelitian menggunakan desain studi cross-sectional. Sampel berjumlah 261 anak dipilih dengan menggunakan multistage random sampling dari 13 puskesmas di enam kelurahan yang berada di tiga kecamatan di Jakarta Pusat. Pengumpulan data dilakukan dengan mengukur berat badan dan tinggi badan serta pengisian kuesioner melalui wawancara yang dilakukan oleh pengumpul data terlatih. Hasil penelitian menunjukkan bahwa prevalensi wasting pada anak umur 6–23 bulan di Jakarta Pusat sebesar 6,9%. Berdasarkan analisis regresi logistik, pemenuhan Minimum Acceptable Diet (MAD) (OR = 3,2 90% CI 1,1-9,5) ditemukan menjadi faktor dominan kejadian wasting selah dikontrol oleh tingkat pendidikan ibu (OR = 1,7 90% CI 0,7– 4.2) dan tingkat pendapatan keluarga (OR = 2.9; 90% CI 0.9-8.9). Penelitian ini menunjukkan perlunya peningkatan perilaku ibu dalam memberikan pengasuhan yang tepat kepada anak. Berdasarkan penelitian ini, kami merekomendasikan agar intervensi praktik pemberian ASI dan MP-ASI yang tepat diperkuat, terutama bagi ibu dengan tingkat pendidikan dan pendapatan keluarga yang rendah.